Protocol for In-vitro Clonal Propagation of Acorus calamus L. an Important Endangered Medicinal Plant - Mazher, Farheen; Sharma, Sonu (Indian Forester, 2012)
Acorus calamus L. (family Acoraceae) a perennial herb is an endangered plant species of medicinal importance. Micropropagation protocol for A. calamushas been standardized. Shoots obtained from the meristems culture on MS medium with BAP (2.0-3.0 mg/l), NAA (0.5-1.0 mg/l), and Kinetin (0.5-1.0 mg/l) in various combinations, showed good results of shoot induction and multiplication in 30 days culture. These shoots were elongated, rooted in-vitro and the plantlets were successfully hardened. The high rate of direct shoot-root multiplication and their high rate of post- hardening survival shows that this protocol could be easily adopted for large scale production.